2016
DOI: 10.1165/rcmb.2015-0297oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway CD8+T Cells Are Associated with Lung Injury during Infant Viral Respiratory Tract Infection

Abstract: Infants and young children are disproportionately susceptible to severe complications from respiratory viruses, although the underlying mechanisms remain unknown. Recent studies show that the T cell response in the lung is important for protective responses to respiratory infections, although details on the infant/pediatric respiratory immune response remain sparse. The objectives of the present study were to characterize the local versus systemic immune response in infants and young children with respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 46 publications
2
49
0
1
Order By: Relevance
“…Experimental RSV infection of adult humans revealed that greater frequencies of virus-specific CD8 T cells in the BAL correlated with reduced clinical disease symptoms [57]. In contrast, a greater ratio of CD8 to CD4 T cells in the airways is associated with acute lung injury during common respiratory tract infections such as RSV [58].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental RSV infection of adult humans revealed that greater frequencies of virus-specific CD8 T cells in the BAL correlated with reduced clinical disease symptoms [57]. In contrast, a greater ratio of CD8 to CD4 T cells in the airways is associated with acute lung injury during common respiratory tract infections such as RSV [58].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the appearance of pathological T cells in adult patients with severe COVID-19 diseases is due to the compensation for this fundamental aging process or not is unclear. At the early stage after birth, CD4 + T cells are impaired in production of Th1 associated proinflammatory cytokines and skewed toward Th2 (67). CD8 + T cells reduced expression of cytotoxic and inflammatory mediators.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Increased T‐cell production of ROS, coupled with neonates’ diminished free‐radical scavenging capabilities, damages the lung . Prolonged recruitment and survival of neutrophils due to increased IL‐8 from neonatal T cells plays a role in tissue damage in the lungs . Infants who develop acute lung injury have been shown to have a higher level of IL‐6 and increased CD8:CD4 ratio in the lung during injury and infection …”
Section: Human Neonatal Cd8+ T Cells Display Innate‐like Featuresmentioning
confidence: 99%
“…99 Prolonged recruitment and survival of neutrophils due to increased IL-8 from neonatal T cells plays a role in tissue damage in the lungs. 97,100 Infants who develop acute lung injury have been shown to have a higher level of IL-6 and increased CD8:CD4 ratio in the lung during injury and infection. 100…”
Section: F I G U R E 2 Phenotypic Differences Of Neonatal and Adult Cmentioning
confidence: 99%